The Implementation of Online Project-Based Learning Model With A Combination of Collaborative Learning to Improve The Learning Result of Digital Photo Composition - Anita Dian Susanti; Basori Basori; Agus Efendi (Pendidikan Teknik Informatika dan Komputer, Universitas Sebelas Maret, 2018)
The purpose of this research was to improve the learning results of Digital Photo Composition through the implementation of Online Project Based Learning model with a combination of Collaborative Learning on Multimedia students of SMK Negeri Takeran. This research was Classroom Action Research (CAR) with the cycle model of collaboration between researcher dan teacher. This survey was conducted in two cycles with each cycle consisting of planning, acting, observing, and reflecting. These subjects were students of Multimedia eleventh grade of SMK Negeri Takeran, which consisted of 22 students. The data collection technique was a test, observation, interview, and documentation. The data validity tests of the research were a triangulation of source and triangulation of method. The data analyzed technique was quantitative-descriptive analysis technique. Based on the result of this survey, it could conclude that implementation of Online Project Based Learning model with a combination of Collaborative Learning can improve learning result at Multimedia eleventh grade of SMK Negeri Takeran. It proved by the increase of average scores in the cognitive test for each cycle. The average value of pra-cycle was 69,82 with the completeness of 22,73% or 5 of 22 students. While on the cycle I was 77,5 with the completeness of 63,64% or 14 of 22 students. The average score of cycle II was 83,95 with the integrity of 81,82% or 18 of 22 students.